2022
DOI: 10.1186/s12882-021-02659-6
|View full text |Cite
|
Sign up to set email alerts
|

The association between olfactory and gustatory dysfunction and chronic kidney disease

Abstract: Background Olfactory and gustatory changes may contribute to poor appetite and food aversion in chronic kidney disease (CKD), though the prevalence of olfactory and gustatory dysfunction is not known in the CKD population. Methods We conducted a cross-sectional study among 3527 US adults aged ≥40 years old in the National Health and Nutrition Examination Survey (NHANES) between 2013 and 2014. We measured the prevalence of olfactory and gustatory dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…A review of the literature showed that despite differences, there was consistently a high prevalence of altered taste (31%-80%) and smell (30%-56%) among hemodialysis patients. [4][5][6] The reason for the differences between these prevalences can be explained by the different measurement methods used in the evaluation of altered taste and smell in studies (visual analogue scale, electrogustometry, taste strips, sniffing sticks, multiple liquid stimuli, etc.). In this study, the TSDQ, which has been validated and found reliable in hemodialysis patients, was used.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A review of the literature showed that despite differences, there was consistently a high prevalence of altered taste (31%-80%) and smell (30%-56%) among hemodialysis patients. [4][5][6] The reason for the differences between these prevalences can be explained by the different measurement methods used in the evaluation of altered taste and smell in studies (visual analogue scale, electrogustometry, taste strips, sniffing sticks, multiple liquid stimuli, etc.). In this study, the TSDQ, which has been validated and found reliable in hemodialysis patients, was used.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of these symptoms can lead to malnutrition. 5 In a review of the literature, three studies were found on altered taste and the nutritional status of hemodialysis patients. 2,32,33 These studies showed a high prevalence of an altered taste and a significant association between altered taste, upper gastrointestinal symptoms (nausea, vomiting, anorexia, dry mouth, and pain), and malnutrition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations